The Relationship Between Adolescent Emotional Maturity and Self-Adjustment in Indonesia - Desi Harlina; Zadrian Ardi (Jurnal Neo Konseling, 2021)
Adolescence is a period where individuals have high emotional tension, especially social pressure and new conditions. Therefore, teenagers often find it difficult to adjust to the environment and the problems that occur to them. Difficulties in adjustment experienced by adolescents are influenced by several factors, one of which is emotional maturity. Adolescents are said to have reached emotional maturity if they do not explode their emotions in front of others, assess the situation critically, display appropriate reactions according to the situation in their social environment. Adolescents who master emotions well can control themselves over their environment so that they are able to adapt to existing conditions. The purpose of this study is to describe the condition of emotional maturity and adolescent adjustment. The sample in this study was 241 students from SMAN 4 Padang. Sampling using Statified Random Sampling technique. The findings of this study are, emotional maturity in the high category, adolescent self-adjustment in the high category, there is a significant positive relationship between emotional maturity and adolescent self-adjustment